The Role of Family Counseling in Developing Children's Mental Health - Azka Dhianti Putri; Ineu Silviany; Nadia Aulia Nadhirah; Nani M. Sugandhi (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2023)
The role of the family is very important in building children's mental health and preventing children's mental disorders. The family is the smallest unit in society which plays an important role in children's education, where interaction and communication occur by sharing love, happiness, and sadness so that it is closely related to the child's development process. Therefore, family counseling is very important in helping to improve the system within the family, where this system will greatly influence the child's mental health. Family counseling is a process of assistance provided by counselors to help clients as family members through the family system to solve problems by improving communication or the family system so that the family can return to being functional and harmonious. So the role of family counseling is very important in developing children's mental health, one of which is its role in restructuring the family unit which is very important in building children's mental health. This scientific paper uses the literature review method by exploring several journals, books, and documents, both printed and electronic, as well as other sources of data or information relevant to the study.